Political parties, parliaments and legislative speechmaking - Bäck, Hanna 1975-; Debus, Marc 1978- (Palgrave Macmillan, 2016)
"Why do some Members of Parliament (MPs) take the parliamentary floor and speak more than others? Why do some MPs deviate more than others from the ideological position of their party? This book develops hypotheses on legislative speechmaking and evaluates them by analysing parliamentary debates in seven European democracies: Czech Republic, Estonia, Finland, Germany, Ireland, Norway and Sweden. Assuming that MPs are concerned with policy-making, career advancement, and re-election, the authors discuss various incentives to taking the floor, and elaborate on the role of gender and psychological incentives in speechmaking. They test their expectations on a novel dataset that covers information on the number of speeches held by MPs and on the ideological positions MPs adopted when delivering a speech. "...